Long term stability of immunophenotypic T cell subsets from whole blood of tacrolimus-based therapy kidney transplantation patients and healthy volunteers by flow cytometric analysis - Boonsom, Suthida; Vannaprasaht, Suda; Tassaneeyakul, Wichittra; Wongratanacheewin, Surasakdi; Kaewraemruaen, Chamraj (Asia-Pacific Journal of Science and Technology, 2019)
Flow cytometric analysis has become popular in immunology to identify T cells subsets. Unfortunately, using this technique has been limited by requiring testing blood samples within 24 hours after collection. Therefore, preserving the stability of lymphocytes may be useful to prolong blood samples before analysis by flow cytometry. The aim of this study was to validate long term stability of T cell subsets (cell surface markers, CD3+, CD3+CD4+ and CD3+CD8+, and intracellular marker, CD4+IL-2) by flow cytometric technique using whole blood samples from tacrolimus-based therapy kidney transplantation patients and healthy volunteers. Whole blood samples were collected from 10 tacrolimus-based therapy kidney transplantation patients and 10 healthy volunteers, separated into 2 groups by stored at 4 ̊C and -20 ̊C, and then analyzed by flow cytometry at day 1, day 3, day 7, day 15 and day 30 after collection. The percentage of T cell subsets were recorded at each time interval. The percentage of CD3+CD4+ subset in patient group was not significantly different up to 30 days after blood sample collection storage in both 4 ̊C (day 1 = 45.88 ± 4.78 VS day 30 = 41.32 ± 4.03) and -20 ̊C (day 1 = 42.76 ± 3.54 VS day 30 = 38.52 ± 2.97), P > 0.05. CD3+, CD3+CD8+, and CD4+IL-2 subset were not significantly different in both groups. Moreover, CD3+, CD3+CD4+, CD3+CD8+, and CD4+IL-2 subsets were significantly different between patient and healthy groups. These findings indicate that whole blood samples could preserve all cells for 30 days before flow cytometric analysis is done for both the patient and the healthy group.